The role of endocrine factors in diagnostics of thyroid cancer by sonoelastography - D. A. Vasilyev; E. V. Kostromina; Z. A. Radzhabova; L. A. Krasilnikova; D. A. Rakitina; A. V. Gurin; R. A. Nazhmudinov; I. V. Dunaevskiy; L. M. Berstein (Опухоли головы и шеи, 2015)
The role of real-time elastography or sonoelastography has been widely discussed recently. However, there are practically no publications which showed the influence of endocrine status in the process for improving of diagnostic value of this method; this issue was the aim of our study. 128 patients (31 – benign adenomas and 97 – thyroid cancer: 13 – follicular and 84 – papillary) were evaluated prospectively. Mean age was 48.3 ± 15.9 years. It was confirmed that the blue colour or 4–5 elastotype of sonoelastography was mainly discovered in thyroid cancer vs adenoma (73.2 % vs 25.8 %, χ2 = 18.96, р = 0.0001). Parameters of the sensitivity, specificity and accuracy were equal 90.7 %, 54.8 % and 82.0 % for sonoelastography, and 95.9 %, 45.2 % and 83.6 % for fine-needle aspiration biopsy, respectively. The combination of sonoelastography with fine-needle aspiration biopsy or with body mass index, presurgical glucose or thyroid-stimulating hormone level increased specificity of sonoelastography by 65.0 %, 70.0 %, 64.7 % and 63.2 %, respectively. Thus, sonoelastography had the same diagnostic accuracy as fine-needle aspiration biopsy in predicting of thyroid cancer. The specificity of sonoelastography could be increased by combination with fine-needle aspiration biopsy as well as thyroid-stimulating hormone or glucose level and body mass index value.